Plenty to Admire...in Today's Dry Cleaning! - Dow Chemical Company (1946)
Color print advertisement for Dowclene synthetic solvents manufactured and sold by the Dow Chemical Company for use in dry-cleaning, among other applications. The advertisement depicts a woman holding up a freshly-cleaned garment, while two men look suggestively in her direction.
Keywords: Chemical industry; Dow Chemical Company; Dry cleaning; Corporations; Advertising; Dry cleaning industry; Solvents; Advertising, Industrial; Women in advertising